The tumour microenvironment influences antigen specific T cell transmigration - Popple, Amy Lee (2012)
T cell infiltration into tumours is essential for tumour antigen recognition and tumour cell elimination. The aim of this study was to develop a better understanding of T cell infiltration into tumours, focusing on two opposing arms of an immune response, anti-tumour CD8 Tcells and Regulatory T cells (Tregs). Activated CD4 T helper cells are also of importance but could not be studied due to the time constraints of the project. The effect of T cell signalling at the immunological synapse following interactions between T cells and APCs presenting cognate antigen have been well studied [1]. The endothelium is neither a stereotypical APC nor simply a passive filter barrier for non-cognate infiltrating T cells. The endothelium can activel influence the development of an inflammatory response depending on the functional state of both the endothelium and interacting T cells (resting versus recently activated T cells)and the type of interactions (cognate versus non-cognate). The hypothesis was that recognition of antigens presented in the context of major histocompatibility complex (MHC)molecules by endothelium aids T cell transmigration and hence infiltration into tissues, including into tumours.